A Business Case Study on Aspiring Rural Giant - The Mishra's - Pandey, Rajesh Kumar; Avinash Mishra, (Management Journal for Advanced Research, 2023)
Retail Industry is one among the leading sectors in the Nation. The Investors in Retail sector have been in the positive sphere provided they match to the demand – supply avenues. Another prominent Sector in the Nation is the LPG Sector. The same falls under necessity and the Government has been pretty concerned with the LPG Industry and its promotion. This Case is about a Family run business with family members being the Partners to the businesses in the Retail & LPG sectors. The Businesses of the Family is located at Majhauli Road, Prangarhi, Mairwa, Dist. Siwan, Bihar - 841239. The LPG Business is run under the name of Baba Consultancy & Company (BC & C) Indane Gas Agency and the Retail business with Parent name as M-Retail with operation of franchise business – Citi Megamart. The Case study reflects the Rural challenges for the business with context to LPG and Retail Business. The case expects the resolution pertaining to its future operations and analyzing its diversification decisions. The present case is a type of Teaching case with a focus on the Illustrative & Appraisal Case approach. The Mishra’s (Partners) are progressing well with more of aspirations for their business. In the year 2022-23 the business is now into the business appraisal process.